STILLBIRTHS: WHAT CAN BE DONE TO CONFRONT AN INVISIBLE PUBLIC HEALTH PROBLEM IN PAKISTAN? - Shaikh, Babar Tasneem; Hafeez, Assad; Hamid, Saima (Journal of Ayub Medical College Abbottabad, 2017)
Pakistan has been ranked highest and appears worst in stillbirths' rate according to the recent global estimates. Reasons could be manifold; socio-cultural, health system related country specific, and some of these of course dÃ©jÃ  vu, i.e., the biomedical causes. Yet, a fresh stocktaking is necessary to understand the complex phenomenon in a country, awfully affected by this menace. Maternal, neonatal and child health program needs to be informed and geared up toward addressing the actual reasons behind this heavy toll of stillbirths inPakistan. Maternal health indicators would never be improved, if the issue of stillbirths is not stalled at the earliest. Besides known medical reasons, this account attempts to document the health systems related factors, and more so the social determinants behind the whole scenario, so that appropriate and customized interventions could be suggested, developed and implemented. This paper will be a piece of evidence for policy corridors, program managers, development partners, non-governmental organizations, public health institutions, students, and researchers to enhance their understanding of a major public health problem, and to recognize the strengths and opportunities in the health system of Pakistan to cope with this challenge. Keywords: Stillbirths; Health system; Social determinants; MNCH; Pakistan